(Castres) L'Adoration des Mages - Alejo Fernandez - Musée Goya - Didier Descouens (Wikimedia Commons, 2024)
Notice iconographique issue de Wikimedia Commons. Titre: (Castres) L'Adoration des Mages - Alejo Fernandez - Musée Goya. Alejo Fernández, The Adoration of the Magi, first quarter of the 16th century. Goya Museum, France.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures